The spatial and temporal variation of the terrestrial water storage anomaly (TWSA) of Iraq for the period 2002–2019 based on GRACE gravity data - Al-Abadi A.M.; Al-Mohammdawi J.A.; Abass A.K. (Kuwait Journal of Science)
This study utilized data from the NASA Gravity Recovery and Climate Experiment (GRACE) to examine the variability of the terrestrial water storage anomaly (TWSA) in Iraq between 2002 and 2019. The analysis focused on six grid cells representing the Iraqi territory. The season trend decomposition (SLT) method was used to decompose the signal time series of TWSA to reveal the seasonality, trend, and random noise for the six GRACE blocks. Results proved that Block01 in northwestern side of Iraq, experienced a significant reduction in TWS between 2002 and 2009, followed by a negative linear trend until 2015, and then a positive trend. Block02 which is located in the northeastern part of Iraq showed a decreasing trend in TWS until 2008, after which it had a positive trend. Block03 in the western central side of Iraq reveals a decrease in TWS from 2002 to 2008, followed by a negative linear trend until 2016, and then a positive trend. Block04 in the eastern Mesopotamian plain had a minor increase in TWS until 2006, followed by a substantial decrease until 2016, before stabilizing and showing a positive trend. Block05 in the southwestern side of Iraq demonstrated a continuous decline in TWSA. In contrast, TWS increased in block6 on the southeastern side from 2002 to 2007, then decreased from 2007 to 2009. TWSA levels remained stable from 2009 to 2016, then increased from 2016 to the end of 2019. The seasonal fluctuations in TWS varied across the blocks, but generally, surpluses were observed in winter and spring, while deficits were observed in summer and autumn. The shortage in TWS is attributed to drought and excessive use of groundwater for irrigation. The recent positive trends in TWS in some blocks suggest that the drought may be coming to an end, but further analysis is necessary to reach a definitive conclusion. © 2024 The Authors